The World is Here. Romualdas Ozolas interviewed by Algimantas Jankauskas and Jūratė Kavaliauskaitė - Jankauskas, Algimantas; Kavaliauskaitė, Jūratė (Problemos, 2018)
[text in Lithuanian]Romualdas Ozolas interviewed by Algimantas Jankauskas and Jūratė Kavaliauskaitė. Vilnius, May 26, 2011.Document: audiorecord (92 min.), privat collection of A. Jankauskas.
Keywords: none